Conditions and Challenges for Building Startup Ecosystems: Recommendations Regarding Public Support for Startup Ecosystems in Poland - Marta CZYŻEWSKA (Communications of International Proceedings, 2021)
The article aims to analyze selected factors determining the development of startup ecosystems on the example of Poland. The theoretical part presents the definitions of a startup and startup ecosystem. Factors influencing the development of startup-friendly ecosystems, which significantly affect the innovation of global economies, were identified. The article presents the conclusions of the research conducted in 2020-2021 by the author independently and in cooperation with other researchers, based on which recommendations for decision-makers were formulated to support the startups ecosystem development in Poland. The results and recommendations can serve as a base for comparative analyzes of startup ecosystems in other countries in Europe and in the world, as well as an invitation to cooperation and discussion on the directions of activities improving the functioning of startup ecosystems.
Keywords: Innovative Entrepreneurship; Startups; Startup Ecosystem; Business Incubation; Acceleration Programs; Venture Capital Funds